THU0030 IL-2IC suppresses CIA in mice by the TH1/TH17 immune responses due to enhancement of both treg numbers and treg functions. (15th June 2017) - Yokoyama, Y; Iwasaki, T; Kitano, S; Furukawa, T; Satake, A; Matsui, K; Sano, H
Abstract : Background: Interleukin-2 (IL-2) induces regulatory T cells (Tregs) and reduces disease activity such as graft versus-host disease and systemic lupus erythematosus. IL-2/anti-IL-2 monoclonal antibody immune complex (IL-2IC) increases the half-life of IL-2 in vivo and specifically induces Tregs. We previously demonstrated that administration of IL-2IC suppressed collagen-induced arthritis (CIA) in mice (EULAR 2015). Objectives: To clarify complex regulatory network of IL-2IC in autoimmune arthritis, we examined the suppression mechanism of IL-2IC induced Tregs to Th1 and Th17. Methods: Male DBA/1 mice were immunized by injection of 200μg of Type II collagen emulsified with an equal volume of complete Freud adjuvant intradermally at the base of the tail of mice (first immunization). Second immunization was given 21 days after first immunization. IL-2ICs were prepared by mixing 5μg of anti-IL-2 antibody (clone JES6–1D) with 1μg of mouse IL-2 for 15 minutes. The mice were injected with either PBS as a control or IL-2IC (5μg /mouse) intraperitoneally for 3 days. Mouse paws were scored for arthritis using a macroscopic scoring system ranging from 0 to 4 (0, no swelling or redness; 1, swelling/redness of paw or one joint; 2, two joints involved; 3, more than two joints involved; and 4, severe arthritis of the entire paw and joints). The arthritic score for each mouse is the sum of the scores of all four paws. Peripheral blood cells were stained with anti-CD25 (PC61), anti–CD4 (RM4–5), anti-Foxp3 (FJK-16s) and CD4+CD25+Foxp3+ Tregs were analyzed by flow cytometry. Th1 and Th17 cells infiltrating in the synovium were examine by immunohistochemistry stained with anti-IFN-g and IL-17 mAb. CD4+CD25+ Treg cells were analyzed for suppressive activity against proliferation of effector CD4+ T cells. For intracellular cytokine staining, spleen cells which were removed in day 28, were stimulated with PMA, ionomycin, and breferdin for 6 hours and intracellular cytokine staining were performed by using anti-IFN-γ, anti-IL-10, anti-IL-17, and analyzed by flow cytometry. Results: To define the effects of IL-2IC on established CIA, IL-2IC was administered for 3 days from day 21 to day 23 after the first immunization (day 0 to day 2 after the second immunization) of CIA. To define the effect of IL-2IC on early stages of disease induction we administered IL-2IC from day 0 to day 2 after first immunization. We observed a significant decrease in both the incidence and severity of arthritis in these CIA mice. Injection of IL-2IC effectively elicited more than 2-fold expansion of CD4+CD25+Foxp3+ Tregs in peripheral blood cells than control mice. Th1 and Th17 cells infiltrations in the synovium were significantly inhibited by IL-2IC treatment. In vitro suppression assay demonstrated significant augmentation of the suppressive capacity of CD4+CD25+Treg cells in IL-2IC treated mice. Intracellular cytokine staining revealed that IL-10 production by CD4+ cells in IL-2IC treated spleen increased four folds than in controls, and IFN-γ-producing helper T cells (Th1) and IL-17-producing helper T cells (TH17) were significantly decreased. Conclusions: These observations indicate that IL-2IC not only induce Tregs, but also augments Treg function by enhancing IL-10 production. Thereby Tregs suppress Th1 and Th17 cells. Disclosure of Interest: None declared